Răspuns :
3 x [ 90 : 45 + 2 x ( 69 : 23 + 10 ) ] + 105 : 3=119
=3 x [ 2 + 2 x ( 3 + 10 ) ] + 35=
= 3 x ( 2 + 2 x 13 ) + 35 =
= 3 x ( 2 + 26 ) + 35 =
= 3 x 28 + 35 =
= 84 + 35 =
= 119
=3 x [ 2 + 2 x ( 3 + 10 ) ] + 35=
= 3 x ( 2 + 2 x 13 ) + 35 =
= 3 x ( 2 + 26 ) + 35 =
= 3 x 28 + 35 =
= 84 + 35 =
= 119
3 × [ 90 : 45 + 2 × ( 69 : 23 + 10 ) ] + 105 : 3 = 119
= 3 × [ 2 + 2 × ( 3 + 10 ) ] + 35
= 3 × ( 2 + 2 × 13 ) + 35
= 3 × ( 2 + 26 ) + 35
= 3 × 28 + 35
= 84 + 35
= 119
= 3 × [ 2 + 2 × ( 3 + 10 ) ] + 35
= 3 × ( 2 + 2 × 13 ) + 35
= 3 × ( 2 + 26 ) + 35
= 3 × 28 + 35
= 84 + 35
= 119